Pattern of Renal Cell Carcinoma – A Single Center Experience in Nepal. - Sidharth, Mr; Luitel, B R; Gupta, D K; Maskey, P; Chalise, P R; Sharma, U K; Gyawali, P R; Shrestha, G K; Sayami, G; Joshi, B R (Kathmandu University Medical Journal, 2012)
Background Renal tumor is the 13th most common malignancy in the world and more than 90% of renal tumors are renal cell carcinomas. As there is no data available on renal cell carcinoma in Nepal, hence this study was undertaken to analyze the patterns of renal cell carcinoma in patients with renal mass at a tertiary level hospital in Nepal. Objectives To analyze the patterns of renal cell carcinoma in patients with renal mass at a tertiary level hospital in Nepal. Methods The case records of 50 consecutive patients with renal cell carcinoma presenting at the Tribhuvan University Teaching Hospital, Kathmandu from July 2006 to June 2011 were retrospectively evaluated for presenting symptoms, physical finding, investigation and histopathology report. Results Out of 50 patients, 64% were male and 36% were female. The age ranged between 11 to 78 years (mean ± SD: 55 ± 15 years). Fifty four percent of patients were smokers. Incidentally tumor was detected in 40% cases by ultrasonography and the typical triad was present in only 4%. The tumor was occupying upper pole in 40% of cases. The tumor size ranged from 3 to 15 cm (mean ± SD: 7.3 ± 2.9 cm). Histopathologically, 76% of the patient had organ confined renal cell carcinoma (T1-2 N0 M0). Clear cell was the most common type seen in 86%. Fuhrman’s nuclear grade 2 was found in 50%. Conclusion Many of the renal cell carcinoma are detected incidentally, at an early stage and are of clear cell subtype. DOI: http://dx.doi.org/10.3126/kumj.v9i3.6302 Kathmandu Univ Med J 2011;9(3):185-8